Spatial coherence of room-temperature monolayer WSe2 exciton-polaritons in a trap - Hangyong Shan (Nature Portfolio, 2021)
Here, the authors show that the interaction between microcavity photons and excitons in an atomically thin WSe2 results in a hybridized regime of strong light-matter coupling. Coherence build-up is accompanied by a threshold-like behaviour of the emitted light intensity, which is a fingerprint of a polariton laser effect.